Apparent diffusion coefficient quantification as an early imaging biomarker of response and predictor of survival following yttrium-90 radioembolization for unresectable infiltrative hepatocellular carcinoma with portal vein thrombosis. - Kokabi, Nima; Camacho, Juan C; Xing, Minzhi; Qiu, Deqiang; Kitajima, Hiroumi; Mittal, Pardeep K; Kim, Hyun S (Abdominal Imaging, 2014)
Purpose: To investigate early diffusion-weighted imaging (DWI) at 30-days post-yttrium-90 (Y-90) radioembolization as a predictor of treatment response and survival in unresectable infiltrative hepatocellular carcinoma (HCC) with portal vein thrombosis (PVT).Materials and Methods: In a prospective study, 18 consecutive patients with unresectable infiltrative HCC and PVT underwent Y-90 therapy. MR imaging was obtained pre Y-90, and at 1 and 3 months post-therapy with DWI fat-suppressed tri-directional diffusion gradient (b = 50, 400, 800 s/mm(2)). Response was evaluated using target mRECIST and EASL. Relative change in apparent diffusion coefficient (ADC) value of tumors was evaluated. Statistical analysis using receiver operator characteristic curves was performed. Paired t test and Pearson correlation coefficient (r) were used to assess intra- and inter-observer variability. Survival analysis was performed using Kaplan-Meier estimation and log-rank test.Results: Mean ADC values of all HCC's at baseline and at 30-days post-Y90 therapy was 0.86 × 10(-3) and 1.17×10(-3) mm(2)/s, respectively (p < 0.001). Tumors with objective response by mRECIST had significantly increased ADC value when compared to "non-responders" (1.27 vs. 1.05×10(-3) mm(2)/s, p = 0.002). A >30% increase in ADC value at 30-days was found to be at least 90% sensitive in predicting response at 90 days. A >30% increase in ADC value at 30-days predicted significantly prolonged survival.Conclusion: A 30% increase in ADC value at 30-days measured post Y90 is a reproducible early imaging response biomarker predicting tumor response and prolonged survival following Y-90 therapy in infiltrative HCC with PVT.